Building a Picture of Usage Patterns in a Language Learning Space: Gathering Useful Quantitative and Qualitative Data - Katherine Thornton; Nao Noguchi (Studies in Self-Access Learning Journal, 2016)
While evaluation of a language learning space can be a difficult undertaking, it is possible to design evaluation instruments that both satisfy institutional demands for numeric data and also provide useful information that can be used to improve the space. This paper reports on the implementation, one quantitative and one qualitative, of two evaluation instruments at a small and relatively new self-access centre in Osaka, Japan. The area counting system gives rich data about how students are using the space, while the user experience survey provides much valued learner voices on different aspects of the space and its mission. Examples are given from the findings and how this data can be utilised to enhance the space itself.